Using a styles of participation self-classification measure to characterize highly specialized anglers: Styles of participation. Issue 1 (2nd January 2023) - Smith, William E.; Kyle, Gerard T.; Sutton, Steven
ABSTRACT: The purpose of our study was to develop a measure of angling guides' contextual styles of participation and investigate its ability for revealing heterogeneity among this highly specialized population. Data drawn from a sample ( n = 391) of licensed Texas Gulf Coast inshore fishing guides revealed that a self-classification measure that explicitly identified attributes of the preferred style of fishing, such as bait, tackle, and technique, was effective in revealing heterogeneity more so than other behavioral and commitment-based indicators. In the context of our sample and study population, the findings further demonstrated the efficacy of self-classification measures for revealing heterogeneity, but also pointed toward the need for in-depth contextual insight when working with populations that are clearly distinct from for the general population.